Melatonin Accumulation in Sweet Cherry and Its Influence on Fruit Quality and Antioxidant Properties - Hui Xia; Yanqiu Shen; Tian Shen; Xin Wang; Xuefeng Zhang; Peng Hu; Dong Liang; Lijin Lin; Honghong Deng; Jin Wang; Qunxian Deng; Xiulan Lv (Molecules, 2020)
Although the effects of melatonin on plant abiotic and biotic stress resistance have been explored in recent decades, the accumulation of endogenous melatonin in plants and its influence on fruit quality remains unclear. In the present study, melatonin accumulation levels and the expression profiles of five synthesis genes were investigated during fruit and leaf development in sweet cherry (Prunus avium L.). Melatonin was strongly accumulated in young fruits and leaves, then decreased steadily with maturation. Transcript levels of PacTDC and PacSNAT were highly correlated with melatonin content in both fruit and leaves, indicating their importance in melatonin accumulation. Furthermore, application of 50 and 100 μmol·L−1 of melatonin to leaves had a greater influence on fruit quality than treatments applied to fruits, by significantly improving fruit weight, soluble solids content, and phenolic content including total phenols, flavanols, total anthocyanins, and ascorbic acid. Meanwhile, melatonin application promoted the antioxidant capacity of fruit assayed by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azinobis (3-ethylben zothiazoline-6-sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP). These results provide insights into the physiological and molecular mechanisms underlying melatonin metabolism of sweet cherry.